THE INFLUENCE OF RELATIONSHIP MARKETING AND BRAND IMAGE ON CUSTOMER LOYALTY AT ATHIFAH KENDARI SOUVENIR STORE - Rachmani, Athifah; Haerani, Siti; Toaha, Muhammad (Accounting Profession Journal (APAJI), 2024)
This study aims to determine the effect of Relationship Marketing and Brand Image on Customer Loyalty at ATHIFAH Kendari SouvenirStore. This type of research uses quantitative research. The population in this study is the consumers of ATHIFAH Kendari SouvenirStore whose number is unknown (infinite). The sample in this study amounted to 50 respondents. The sampling technique in this research is by using purposive sampling. The method of data collection in this study was using an online questionnaire, namely through the google form. This study uses multiple linear regression analysis. The results of this study indicate that: (1) relationship marketing and brand image have a positive and significant effect on customer loyalty simultaneously (2) relationship marketing has a positive and significant effect on customer loyalty partially (3) brand image has a positive and significant effect on customer loyalty partially.